Dr. Bouraoui Kotti — Deep Plane Facelift — Dubai - Kotti, Bouraoui (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Bouraoui Kotti, practicing in Dubai, UAE. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003019; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; uae; dubai